Saving America's school infrastructure - Crampton, Faith E.; Thompson, David C., 1951-; Kennedy, Edward M. (Research in education fiscal policy and practice., 2003)
This book is divided into four parts: overview and scope of the problem; current challenges to funding of school infrastructure; the future of school infrastructure funding; and conclusion.